2001
DOI: 10.1038/sj.cdd.4400962
|View full text |Cite
|
Sign up to set email alerts
|

Human ΔNp73 regulates a dominant negative feedback loop for TAp73 and p53

Abstract: Inactivation of the tumour suppressor p53 is the most common defect in cancer cells. p53 is a sequence specific transcription factor that is activated in response to various forms of genotoxic stress to induce cell cycle arrest and apoptosis. Induction of p53 is subjected to complex and strict control through several pathways, as it will often determine cellular fate. The p73 protein shares strong structural and functional similarities with p53 such as the potential to activate p53 responsive genes and the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
336
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(365 citation statements)
references
References 44 publications
23
336
3
3
Order By: Relevance
“…We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a). Such a dominant-negative function of DNp73 has also been observed in this study with respect to hTERT regulation.…”
Section: Regulation Of Htert By P73 M Beitzinger Et Alsupporting
confidence: 80%
See 1 more Smart Citation
“…We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a). Such a dominant-negative function of DNp73 has also been observed in this study with respect to hTERT regulation.…”
Section: Regulation Of Htert By P73 M Beitzinger Et Alsupporting
confidence: 80%
“…In contrast to downregulation of hTERT by differentiation or proapoptotic stress signals, hTERT is typically activated in immortal cells and established tumors . We and other groups have recently demonstrated that tumor cells frequently overexpress N-terminally truncated p73 isoforms that result from abberant splicing or the use of an alternative intronic promoter (Fillippovich et al, 2001;Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a, b;Zaika et al, 2002;Pu¨tzer et al, 2003). These DNp73 proteins act as dominant-negative inhibitors of the proapoptotic p53 family members by formation of transactivation-defective heteromeric complexes (Grob et al, 2001;Kartasheva et al, 2002;Stiewe et al, 2002a).…”
Section: Regulation Of Htert By P73 M Beitzinger Et Almentioning
confidence: 99%
“…Each isoform is also subject to extensive alternative splicing at the 3 0 -end of mRNA, resulting in up to 24 transcripts, able to promote or repress apoptosis to different extents (De Laurenzi et al, 1998;Yang et al, 2000). The proteins originating from the second promoter, DNp73, have a dominant negative activity on the tumor suppressor functions of both TAp73 and p53 and this regulatory loop has been implicated in tumorigenesis (Grob et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] They act as powerful inhibitors of p53 and TAp73 since they retain their DNA-binding and tetramerization competence. [7][8][9]11,13,14 In cultured cells, DNp73 abrogates the suppressive activity of p53 and TAp73 and inactivates their ability to induce apoptosis and cell cycle arrest. 9 DNp73 overexpression results in malignant transformation of immortalized NIH3T3 fibroblasts 8 and also promotes immortalization in primary cells and cooperates with oncogenic Ras in driving their transformation in vivo.…”
mentioning
confidence: 99%
“…Also, the relative longevity of DNp73 versus TAp73 proteins, when in isolation, supports previous anecdotal observations that DNp73 proteins are more stable than TAp73 in tumors. 13,19 We next tested whether DNp73 proteins can induce stabilization of TAp73 proteins. H1299 cells were transfected with either TAp73a or b alone, or cotransfected with the same amount of TAp73a or b plus increasing amounts of DNp73a or stabilization, possibly because the levels of DNp73a are often higher than DNp73 which might in turn be related to the longer half life of DNp73a compared to b.…”
mentioning
confidence: 99%